Efeito da funcionalização nas propriedades fotofísicas da MOF UiO-66 - Vinicius Gonçalves Souto Fontenelle (2024)
Given the contemporary environmental challenges, such as global warming and ocean acidification, caused by the constant increase in greenhouse gas emissions, particularly CO₂, it is crucial to develop sustainable methods to mitigate these environmental and social impacts. One alternative for reducing atmospheric CO₂ is the photocatalytic reduction of this molecule using solar energy. This strategy not only reduces atmospheric CO₂ but also transforms a pollutant into high-value-added products. Due to the high bond energy and stability of CO₂, the presence of a catalyst is essential for the reaction to occur. For a material to be used as a photocatalyst, it must absorb as much solar energy as possible, thereby optimizing the use of solar energy as the primary energy source. Metal-organic frameworks (MOFs) are promising materials for this purpose. These materials consist of metal cations and organic ligands that form a porous solid with a high surface area and easily modifiable structure. One of the main advantages of MOFs as photocatalysts is that the organic ligands, acting as antennas, can capture light to generate photoinduced electrons, directly reducing carbon dioxide. Specifically, the MOF UiO-66 is widely used due to its considerable thermal stability. However, this MOF does not exhibit sufficient optical activity to be used as a photocatalyst. Functionalizing this MOF by incorporating functional groups (NH₂) and electron-rich molecules (ferrocene) is an interesting strategy to enhance its catalytic potential. In this study, the MOFs UiO-66, NH₂-UiO-66, and NH₂-UiO-66-Fc were computationally investigated to assess the structural, electronic, and photophysical properties of these materials, with the objective of evaluating their potential as catalysts for the reduction of carbon dioxide. The results indicate that the functionalization and introduction of defects in the MOFs can play a crucial role in improving the photocatalytic efficiency for CO₂ reduction, clearly showing positive effects from the incorporation of ferrocene and amino groups into the structures.